2019
DOI: 10.5194/esd-2019-47
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term Variances of Heavy Precipitation across Central Europe using a Large Ensemble of Regional Climate Model Simulations

Abstract: Widespread flooding events are among the major natural hazards in Central Europe. Such events are usually related to intensive, long-lasting precipitation. Despite some prominent floods during the last three decades (e. g. 1997, 1999, 2002, and 2013), extreme floods are rare and associated with estimated long return periods of more than 100 years. To assess the associated risks of such extreme events, reliable statistics of precipitation and discharge are required. Comprehensive observations, however, are ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…There are already many publications on evaluating the precipitation extremes of RCM output (Jones and Reid, 2001;Räisänen and Joelsson, 2001;Frei et al, 2003;Bell et al, 2004;Scherrer, 2011). It has been shown that the simulated heavy precipitation in RCMs have quite realistic magnitudes in central Europe (Räisänen and Joelsson, 2001;Ehmele et al, 2019), but slightly underestimate observations in southern England and cannot well represent the seasonal extreme precipitation, defined by the high quantile of precipitation intensity over the European Alps (Jones and Reid, 2001;Frei et al, 2003;Bell et al, 2004). With the release of high spatialtemporal resolution RCM outputs, Sunyer et al (2017) evaluated extreme precipitation of seven RCMs at different spatial and temporal aggregations over Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…There are already many publications on evaluating the precipitation extremes of RCM output (Jones and Reid, 2001;Räisänen and Joelsson, 2001;Frei et al, 2003;Bell et al, 2004;Scherrer, 2011). It has been shown that the simulated heavy precipitation in RCMs have quite realistic magnitudes in central Europe (Räisänen and Joelsson, 2001;Ehmele et al, 2019), but slightly underestimate observations in southern England and cannot well represent the seasonal extreme precipitation, defined by the high quantile of precipitation intensity over the European Alps (Jones and Reid, 2001;Frei et al, 2003;Bell et al, 2004). With the release of high spatialtemporal resolution RCM outputs, Sunyer et al (2017) evaluated extreme precipitation of seven RCMs at different spatial and temporal aggregations over Denmark.…”
Section: Introductionmentioning
confidence: 99%